Canoe paddle resonance characteristics and modelling - Runciman, R. J.; Lyle, K.; Patrick, L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
Canoe paddles have been in continuous use for thousands of years. Over that period, the paddle has remained virtually unchanged in basic form and materials. Today, paddles are produced in many different designs by a large number of manufacturers. Prominent within the many factors differentiating the best paddles from the worst is their propensity to resonate during use. This resonance has been so prevalent historically that it has been given its own name: a paddle`s song. The major drawback with paddle resonance is that it is accompanied with the penalty of increased fluid resistance. Paddle manufacturers have long tried to reduce or eliminate paddle resonance, but it is still recognized by paddlers as a significant factor in choosing an optimal paddle.